Utilizing program evaluation processes for strategic learning in nonprofits : Cases of public and volunteer organizations. - Delecour, Tiphaine (My University, 2024)
Strategic evaluation is a tool that organizations can use to evaluate and adapt their strategies, and various tools exist in the business world to do so. Yet, most of the tools that are created deal with the financial perspective as an outcome, leaving nonprofit organizations forgotten as they cannot fully use the existing tools to evaluate their programs, knowing that financial performance is, for them, considered an output. The existing framework within the realm of program evaluation presents evaluation as a means to achieve results that other strategic learning methods cannot; yet, efforts from social organizations to utilize evaluation results towards learning and adaptation of their program often fail. This study investigates how nonprofit organizations could use program evaluation processes to promote strategic learning. The study will explore two views on program evaluation: the theory of change and the utilization-focused evaluation approach. The study constructed a tentative conceptual framework based on primary and secondary data sources. The initial framework was designed with the help of existing theoretical re-search and materials, while the final framework was completed thanks to an empirical study with four participating case organizations. The final framework outlines the general program evaluation processes and strategic learning opportunities nonprofits have when evaluating their programs. The case organizations participating in this study are Bloom Finland, the Multicultural Association of Porvoo, Moni-info Seinäjoki, and International House Oulu. The primary data for the empirical study was gathered with semi-structured interviews with eight decision-makers or presiding board members in nonprofit organizations. The study focused on nonprofit organizations within the specific environment of working with internationals in Finland. The study provided controlled variance between public and volunteer organizations as participants. The findings answered the research question and demonstrated that program evaluation processes can be used for strategic learning in the nonprofit context, although the results showed that adaptations are needed. Altogether, the study recognized eight general program evaluation processes, each linked to their subfactors identified as specifics of the nonprofit organizations. The framework interpreted two theoretical perspectives into one conceptual representation and resulted in a tentative framework to provide evaluators and nonprofits with an evaluation method promoting using the results for strategic learning. The framework remains tentative as real-life tests were not part of this study. The study's conclusion is the framework that can be used to observe whether the program is running as intended and if conditions, actions, users, and uses are appropriately matched.
Keywords: organisations (systems); evaluation; non-profit services; strategic planning; fi=Johtaminen ja organisaatiot|en=Management and Organization|; Master’s Programme in Strategic Business Development